Structured grain trading systems in Africa - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
As Africa’s smallholder farmers are becoming increasingly active players in value chains, there is a corresponding and urgent need to develop more sophisticated trading systems for staple commodities across the continent. Presented with numerous step-by-step figures, tables and boxed examples, this manual clearly describes how structured trading systems work for Africa’s most important staples. It provides a valuable guide to all those involved in creating and running structured trading systems, as well as policy-makers aiming to modernise trading in Africa.